Developing an Integrated Mathematics and Science Module with Merdeka Curriculum for Elementary School - Kharisma Eka Putri; Mumun Nurmilawati; Farida Nurlaila Zunaidah (STAI Hubbulwathan Duri, 2023)
This study aims to develop mathematics and science modules that is intended for prospective elementary school teacher or PGSD Study Program students, to determine the validity of the STEM teaching modules that have been developed, and to find out the practicality of the STEM modules that have been developed. The method was a research and development model using the 4D development model, including the following Define, Design, Develop, and Disseminate. The tryout was carried out on PGSD UNP Kediri students. The data analysis techniques were qualitative and quantitative, embraced with expert and user validation instruments. The results of this study indicate that the STEM teaching modules developed is stated to be very valid or very good and can be used with a score of 3.62 based on the result of validating the math and science modules. To find out the practicality of the teaching modules, validation was carried out on users and tryout. The result shows that the teaching modules developed can be used with a score of 3.50.